Cara Berpikir Orang Jepang: Sebuah Perspektif Budhisme - Anwar, Siti Dahsiar (UI Scholars Hub, 2004)
Buddhism has samsara principle, which means to undergo the life by restraining the hope and desire with the purpose of achieving satori. However, in the Japanese thought tradition, which is natural, pragmatic and realistic, it has been applied and reconstructed from bonno o tatsu (to control the hope and desire) to be bonno o ikasu (to arouse the hope and desire).